2008
DOI: 10.1177/117718010800400113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Learning for Pasifika @ Uoa: a view from the Inside

Abstract: In 2005 the University of Auckland Library established a Pasifika Liaison Librarian position as a new initiative within the existing the Maori Services to enhance the learning of Pasifika students at the University and develop Pasifika Library Support and Information Services. This paper examines the background to the challenge of developing more effective services for Pasifika students and staff within a university institution from the perspectives of Pasifika staff who work in the library. It argues that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…While talanoa is a concept that is part of the daily lives of many Pacific Island communities, it is transferable to a research setting. Several research disciplines or areas are using talanoa including education (Johansson-Fua, 2014; Manu’atu, 2000; McFall-McCaffery, 2008; Otsuka, 2005); literacy (Fletcher et al, 2006); health (Meo-Sewabu, 2015); business (Prescott, 2008); sport (Gordon et al, 2013) housing (Alatini, 2004) and gambling (Guttenbeil-Po’uhila, 2004). Havea (2014) has used talanoa to research climate change in Tonga, whereas our research focused on how Fijian societies might transform in response to climate change.…”
Section: Vanuamentioning
confidence: 99%
“…While talanoa is a concept that is part of the daily lives of many Pacific Island communities, it is transferable to a research setting. Several research disciplines or areas are using talanoa including education (Johansson-Fua, 2014; Manu’atu, 2000; McFall-McCaffery, 2008; Otsuka, 2005); literacy (Fletcher et al, 2006); health (Meo-Sewabu, 2015); business (Prescott, 2008); sport (Gordon et al, 2013) housing (Alatini, 2004) and gambling (Guttenbeil-Po’uhila, 2004). Havea (2014) has used talanoa to research climate change in Tonga, whereas our research focused on how Fijian societies might transform in response to climate change.…”
Section: Vanuamentioning
confidence: 99%
“…Effective teaching practices and transitioning for primary and secondary schools are discussed in the publications of Hawk, Cowley, Hill and Sutherland (2002) and Hill and Hawk (2000). Additionally, tertiary participation, retention, cultural responsiveness and identity are explored (e.g., Chu, 2014;McCaffery, 2008;Porter-Samuels, 2013;Samu, 2006;Spiller, 2013). These researchers tell similar narratives: Pasifika students are underachieving and continue to struggle in mainstream education.…”
Section: Original Articlementioning
confidence: 99%
“…Literature specific to Pasifika students at tertiary institutions speaks to the need for staff to be culturally responsive and for student support initiatives to be diverse to cater for the needs of Pasifika students. This has been accomplished by creating mentoring relationships (Chu, 2014) and enhancing cultural capital by creating Pacific-specific roles (McCaffery, 2008). Mira (2014) examines how the experiences of Samoan woman at tertiary education in Aotearoa New Zealand strengthen or weaken their cultural identity.…”
Section: Original Articlementioning
confidence: 99%
“…A University of Auckland survey (Anae and Suaalii, 1996 as cited in Mara, 2007) found that the General Library was one of the 4 most used services by Pacific students but it needed to be enhanced and extended. The outcome was the development of the Pasifika Liaison Librarian at the University (McFall McCaffery, 2008). In Beaver and Tuck's study (1998) of overseas students at a tertiary institution, Pacific Island students rated their level of competency in 'using the library' very highly, more than Asian students.…”
Section: Pacific People In Educationmentioning
confidence: 99%